The Relationship Between Mother's Attitude and Giving Complete Basic Immunization to Infants Aged 12-24 Months - Lestiani, Lilik; Hilda, Hilda; Ariefah Putri, Rosalin (Rifa'Institute, 2023)
Introduction: Immunizations are important to be given to babies to prevent disease. The complete basic immunization coverage at the Muara Kaman Health Center in 2020 was 65.9%, not reaching the target of 90%. Attitude is one of the factors that influence the low coverage of complete basic immunization. Objective: To determine the relationship between mother's attitude and complete basic immunization in infants aged 12-24 months. Method: This type of research is descriptive analytic with cross sectional design. The sample in this study was a total population of 85 infants aged 12-24 months. Results and Discussion: The characteristics of the respondents were mostly between 20-35 years old (54.1%), multiparity parity (63.6%), secondary education (58.8%) and housewife work (52.9%). The description of the mother's attitude towards giving complete basic immunization is mostly positive, namely 60%. The description of complete basic immunization for infants aged 12-24 months is mostly complete, namely 67.1%. There is a relationship between mother's attitude and complete basic immunization with a p value of 0.000. Conclusion: there is a relationship between mother's attitude and giving complete basic immunization because negative attitudes tend not to pay attention to the schedule of giving complete basic immunization to their babies and positive attitudes will have a greater chance of mothers giving exclusive breastfeeding